2014
DOI: 10.1111/1440-1681.12207
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and neuronal nitric oxide synthases variably modulate the oestrogen‐mediated control of blood pressure and cardiovascular autonomic control

Abstract: Summary We have previously shown that long-term estrogen (E2) replacement lowers blood pressure (BP) and improves the cardiovascular autonomic control in ovariectomized (OVX) rats. In this study, we investigated whether constitutive and/or inducible nitric oxide synthase (NOS) modulate these E2 effects.We evaluated changes in BP, myocardial contractility index (dP/dtmax), and power spectral indices of hemodynamic variability following selective inhibition of eNOS [N5-(1-iminoethyl)-L-ornithine; L-NIO], nNOS (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
3
3
0
Order By: Relevance
“…In fact, as stated above, we demonstrated increased cardiac parasympathetic activity in female but not in male rats exposed to chronic ethanol vapor inhalation [21]. Further, other studies observed that this effect on cardiac vagal tone was estrogen-dependent [36,84,85]. For example, El-mas and Abdel-rahman [36] showed that the parasympathetic overactivity induced by chronic ethanol was exacerbated in estrogen-replaced ovariectomized rats, when compared to ovariectomized ones.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, as stated above, we demonstrated increased cardiac parasympathetic activity in female but not in male rats exposed to chronic ethanol vapor inhalation [21]. Further, other studies observed that this effect on cardiac vagal tone was estrogen-dependent [36,84,85]. For example, El-mas and Abdel-rahman [36] showed that the parasympathetic overactivity induced by chronic ethanol was exacerbated in estrogen-replaced ovariectomized rats, when compared to ovariectomized ones.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, as stated above, we demonstrated increased cardiac parasympathetic activity in female but not in male rats exposed to chronic ethanol vapor inhalation [21]. Furthermore, other studies observed that this effect on cardiac vagal tone was estrogen-dependent [36,104,105]. For example, El-mas and Abdelrahman [36] showed that the parasympathetic overactivity induced by chronic ethanol was exacerbated in estrogen-replaced ovariectomized rats, when compared to ovariectomized ones.…”
Section: Discussionsupporting
confidence: 77%
“…Despite the increased HR, we did not identify changes in MAP of female controls. It has been extensively explained in studies that an estrogen protective effect upon MAP occurs due to its actions in the kidney (e.g., females have higher levels of the vasodilator angiotensin compared to males) (Bhatia et al., ; Brosnihan et al., ; Brown et al., ; Shenoy et al., ; Xue et al., ) and on nitric oxide (NO) production in the heart and vasculature (Abdel‐rahman, ; Caulin‐Glaser et al., ; Chen et al., ; El‐Mas and Abdel‐Rahman, ; Mendelsohn and Karas, ; Wang and Abdel‐Rahman, ). It has also been proposed that although female rats show an increase in HR, the MAP would not be altered because of the sex differences in control of baroreflex responses by the nucleus of the solitary tract (NTS), nucleus ambiguous (NA), parabrachial nucleus (PBN), and caudal and rostral ventrolateral medulla (Abdel‐rahman, ; Mohamed et al., ; Wyss and Carlson, ; Xue et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods to expose rats to alcohol have been used to study the consequences of chronic EtOH exposure on cardiovascular function (Crestani et al., ; El‐Mas and Abdel‐Rahman, ; Engi et al., ; Russ et al., ). However, many studies have demonstrated that alcohol vapor exposure provides a particular advantage over other methods (Gilpin et al., , ; Meinhardt and Sommer, ; Vendruscolo and Roberts, ).…”
mentioning
confidence: 99%